Advanced Antennas for Small Satellites - Gao, Steven; Rahmat-Samii, Yahya; Hodges, Richard E.; Yang, Xue-Xia (Proceedings of the IEEE, 2018)
Antenna is one of the key components onboard small satellites as its design determines the performance of all the wireless systems including telemetry, tracking and control, high-speed data downlink, navigation, intersatellite communications, intrasatellite communications, wireless power transfer, radars and sensors, etc. This paper presents a review of recent development in advanced antennas for small satellites (MiniSat, MicroSat, NanoSat, CubeSat, etc.). A number of recent examples of antennas for small satellite applications are shown and discussed. A conclusion and future development in antennas for small satellites are given in the end.